EXPLAINING MIXED RESULTS ON SCIENCE PARKS PERFORMANCE: BRIGHT AND DARK SIDES OF THE EFFECTS OF INTER-ORGANISATIONAL KNOWLEDGE TRANSFER RELATIONSHIPS - Chan, KYA; Oerlemans, LAG; Pretorius, MW (The South African Journal of Industrial Engineering, 2009)
In the recent past, several researchers explored the added-values of Science Parks. On the